2015
DOI: 10.3892/or.2015.3884
|View full text |Cite
|
Sign up to set email alerts
|

Knockdown of microRNA-1323 restores sensitivity to radiation by suppression of PRKDC activity in radiation-resistant lung cancer cells

Abstract: Abstract.Resistance to radiation is a major problem in cancer treatment. The mechanisms of radioresistance remain poorly understood; however, mounting evidence supports a role for microRNAs (miRNAs) in the modulation of key cellular pathways mediating the response to radiation. The present study aimed to identify specific miRNAs and their effect on radioresistant cells. The global miRNA profile of an established radioresistant lung cancer cell line and the corresponding control cells was determined.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
24
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(24 citation statements)
references
References 34 publications
0
24
0
Order By: Relevance
“…Using next-generation sequencing technology, they revealed miR-371a-5p, miR-34c-5p, and miR-1323 to be overexpressed while miR-324-3p, miR-93-3p, and miR-4501 were downregulated in radioresistant NPC cells [11]. Oncogenic feature of miR-1323 was supported also by Li et al who published that knockdown of miR-1323 restores sensitivity to radiation in radiation-resistant lung cancer cells [71], whereas miR-324-3p has been found downregulated in radioresistant NPC cells and directly targets WNT2B gene [21]. On the other hand, miR-34a, another member of the tumor suppressive miR-34 family, shows rather opposite effect on radioresistance than described in Li et al's study.…”
Section: Involvement Of Mirnas In Radioresistance Of Head and Neckmentioning
confidence: 97%
See 2 more Smart Citations
“…Using next-generation sequencing technology, they revealed miR-371a-5p, miR-34c-5p, and miR-1323 to be overexpressed while miR-324-3p, miR-93-3p, and miR-4501 were downregulated in radioresistant NPC cells [11]. Oncogenic feature of miR-1323 was supported also by Li et al who published that knockdown of miR-1323 restores sensitivity to radiation in radiation-resistant lung cancer cells [71], whereas miR-324-3p has been found downregulated in radioresistant NPC cells and directly targets WNT2B gene [21]. On the other hand, miR-34a, another member of the tumor suppressive miR-34 family, shows rather opposite effect on radioresistance than described in Li et al's study.…”
Section: Involvement Of Mirnas In Radioresistance Of Head and Neckmentioning
confidence: 97%
“…Moreover, our recent study suggests that miR-338-5p sensitizes glioblastoma cells to radiation through regulation of genes involved in DNA damage response such as NDFIP1 (Nedd4 Family Interacting Protein 1), RHEB (RAS homolog enriched in brain), and PPP2R5A (Protein Phosphatase 2 Regulatory Subunit B′, Alph) [70]. In lung cancer loss of miR-1323 and/or miR-18a enhances radiosensitivity whereas miR-511 has been found to suppress growth of radioresistant cell lines [71–73]. More deep study on molecular mechanisms revealed that effect induced by miR-1323 is mainly through the suppressing of PRKDC (Protein Kinase, DNA-Activated, Catalytic Polypeptide) [71].…”
Section: Involvement Of Mirnas In Radioresistance Of Cancermentioning
confidence: 99%
See 1 more Smart Citation
“…Enhanced miR‐15a/16 promoted the radiosensitivity of lung cancer via downregulating the TLR1/NF‐ κ B pathway 60. Knockdown of miR‐1323 restored radiosensitivity by suppression of PRKDC activity in radiation‐resistant lung cancer cells 61. Our findings added another evidence that miR‐18a‐5p was involved in radiosensitivity in lung cancer cells.…”
Section: Discussionmentioning
confidence: 55%
“…Ionizing radiation induces DNA double strand breaks, thus miRNAs that regulate DNA damage and repair signaling pathways have been demonstrated to be involved in radiation sensitivity (27,28). miRNAs involved in cancer stem cell self-renewal, autophagy, hypoxia and survival signaling pathways also affect the radiosensitivity of cancer cells (15,29,30).…”
Section: Discussionmentioning
confidence: 99%